LEXICAL COHESION THROUGH REPETITION IN FOUR SELECTED POEMS FROM THE ANTHOLOGY ”AKU INGIN JADI PELURU” BY WIDJI THUKUL - Abdussalam Jabaruddin Yamjirin; Efid Winarni; Sumarlam (INJOSEDU: International Journal of Social and Education, 2025)
This study investigates the role of lexical cohesion through repetition in Widji Thukul's poetry anthology Aku Ingin Jadi Peluru. Employing a qualitative descriptive approach, it analyzes four selected poems to uncover the types, functions, and meanings of repetition within the texts. The findings reveal the use of four types of repetition: anaphora (25%), epistrophe (25%), mesodiplosis (12.5%), and complete repetition (37.5%). Each type contributes distinctively to enhancing textual cohesion, emphasizing themes, and evoking emotional resonance. For instance, anaphora highlights resilience and societal tensions, while epistrophe underscores economic struggles and class disparities. Complete repetition, the most prominent, portrays cyclical struggles and perseverance, as seen in the repeated phrases "kuhancurkan" and "kubentuk lagi" in the poem Riwayat. Through repetition, Thukul weaves linguistic artistry with ideological critique, transforming his poetry into a medium of resistance and social advocacy. This study expands the understanding of repetition in poetry, offering insights into its aesthetic and rhetorical functions, and invites future research into its applications across cultures and literary genres.